The PRT6 N-degron pathway restricts VERNALIZATION 2 to endogenous hypoxic niches to modulate plant development - Labandera, Anne-Marie (The New phytologist, 2021)
© 2020 The Authors New Phytologist © 2020 New Phytologist Foundation.